Collected Works of C. G. Jung, Volume 17 : Development of Personality - Jung, Carl G. (Book collections on Project MUSE., 2014)
Papers on child psychology, education, and individuation, underlining the overwhelming importance of parents and teachers in the genesis of the intellectual, feeling, and emotional disorders of childhood. The final paper deals with marriage as an aid or obstacle to self-realization.